The Potential of Processing Gambir (Uncaria gambir roxb.) Plants in Mado Laoli Village, Gunungsitoli City - Elva Amurita Zebua; Tety Desrita Handayani; Nathasa Wiesdania Sihite (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2023)
The utilization of the gambier plant in Gunungsitoli City is still limited to produce dried gambier leaves as a raw material for betel nut chewing, so it has the potential to be processed into gambier which has high economic value. The study was aimed to determine the quality of gambier produced from gambier plants that grow in Mado Laoli Village, Gunungsitoli City with different drying methods. This study used a completely randomized design (CRD) consisting of 2 treatments, that were P1 (sun drying) and P2 (oven drying) with 3 replications. The results showed that the gambier plant in Mado Laoli Village had a high potential to be processed into gambier because it has produced gambier which have good quality and met the SNI quality requirements. Sun drying produced gambir second quality (15.48% of water content, 2.37% of ash content, 59.36% of catechin content, 12.17% of tannin content, 5.54% of water insoluble material, 3,29% of alcohol insoluble material). Oven drying produced gambir first quality (11.30% of moisture content, 2.18% of ash content, 68.15% of catechin content, 12.24% of tannin content, 6.32% of water insoluble material, 3.77% of insoluble alcohol). Different drying methods had a significant effect on the yield, moisture content, catechin content, water insoluble material and alcohol insoluble material content.